Exchange Rates and Trade : A Disconnect? - Leigh, Daniel (IMF Working Papers; Working Paper ;, 2017)
We examine the stability and strength of the relationship between exchange rates and trade over time using three alternative approaches, mitigating the endogeneity of the relation. We find that both exchange rate pass-through and the price elasticity of trade volumes are largely stable over time. Economic slack and financial conditions affect the relationship, but there is limited evidence that participation in global value chains has significantly changed the exchange rate-trade relationship over time.